Side viewing micro-endoscope optical system with acromatized objective lens - Doraj-Raj, Nanthakumar (2014)
High resolution microendoscopy (HRME) is a novel optical technique which utilizes optical system to view directly sub-cellular structures. Major obstacles of HRME which uses forward view optical system in achieving high quality image of sub cellular structures in GI tract wall are short depth of field and small field of view. Vibration or movement of the optical system during probing resulted in low image acquisition quality. In this thesis, design and optimization of side view micro endoscope with magnification of 3X optical system using fold mirror,doublets and aspheric lens are presented. Fold mirror incorporated into optical system with a purpose of bending light path which allows GI tract wall viewed side way while rotating for circumferential scanning. In order to minimize aberrations that degrade images created by fold mirror, aspheric lens with conic shape added before fold mirror which functions to collimate rays before reaching fold mirror. Next relationship between working distance, numerical aperture of object and image space and airy disc established to determine magnification and resolution of the optical system. Then 4 doublets lens with varying dispersion ratio used in order to achieve achromatization which functions to increase field of view, working wavelength range, minimizes aberrations and achieved acceptable image qualities. Optimization of optical system performed for optimum performance achievements. Tolerance analysis simulation performed by adding components tolerances in predicting manufacturability of the conceptual design. Simulation results across field of view for wavelength range from 0.53 μm to 0.63 μm presented. Optimum MTF value above 20% recorded for spatial frequency of 240 line/mm at axis. MTF value above 20% recorded for spatial frequency of 170 line/mm at the edge. Maximum drop of 20% of MTF achieved after adding components tolerance limit. This technology can enhance image acquisition quality of HRME while viewing sub cellular tissues such as cytoplasm and nucleus as side view allows circumferential scanning of optical system which simplified movement mechanism. The optical system able to fit into capsule that works as pressure plate to maintain stability. In future developing prototype of the optical system can be used a basis for developing automated circumferential scanning of GI tract.